Automotive accident reconstruction practices and principles - Struble, Donald E. (Donald Edward), 1942-; Struble, John D. (Boca Raton : CRC PRESS, 2020)
This fully updated edition presents practices and principles applicable for the reconstruction of automobile and commercial truck crashes. Like the First Edition, it starts at the very beginning with fundamental principles, information sources, and data gathering and inspection techniques for accident scenes and vehicles. It goes on to show how to analyze photographs and crash test data. The book presents tire fundamentals and shows how to use them in spreadsheet-based reverse trajectory analysis. Such methods are also applied to reconstructing rollover crashes. Impacts with narrow fixed objects are discussed. Impact mechanics, structural dynamics, and conservation-based reconstruction methods are presented. The book contains a comprehensive treatment of crush energy and how to develop structural stiffness properties from crash test data. Computer simulations are reviewed and discussed. Extensively revised, this edition contains new material on side pole impacts. It has entirely new chapters devoted to low-speed impacts, downloading electronic data from vehicles, deriving structural stiffness in side impacts, and incorporating electronic data into accident reconstructions
OCLC-licensed vendor bibliographic record.
Keywords: Traffic accidents; Motor vehicles; Traffic accident investigation; TECHNOLOGY / Engineering / Civil; TECHNOLOGY / Engineering / Mechanical; TECHNOLOGY / Industrial Health & Safety